(untitled) (Dhaka University Journal of Biological Sciences, 2018)
The present study was undertaken to investigate the gender differences in coping styles of patient with depression. Three types of coping styles were measured: problem focused, emotion focused and dysfunctional copings. The sample consisted of 101 participants (Male = 61, 60.4%) and (Female = 40, 39.6%) diagnosed with depression who were selected through convenience sampling technique from different hospitals of Dhaka city. Depression scale (DS), adapted Bengali version of Hospital Anxiety and Depression Scale (HADS) and adapted Bengali version of COPE scale were used to assess different variables for the present study. Results of the study indicated that male patients were tending to use more problem focused coping styles than females and female patients were tending to use more dysfunctional coping style than male. There was no gender difference found in the groups on emotion focused coping style. Based on the findings developing a better therapeutic intervention to treat depression, was discussed. Dhaka Univ. J. Biol. Sci. 27(2): 145-154, 2018 (July)